Functional Use of Directional Local Field Potentials in the Subthalamic Nucleus Deep Brain Stimulation - Telkes, Ilknur; Sabourin, Shelby; Durphy, Jennifer; Adam, Octavian; Sukul, Vishad; Raviv, Nataly; Staudt, Michael D.; Pilitsis, Julie G. (Frontiers in Human Neuroscience, 2020)
Background: Directional deep brain stimulation (DBS) technology aims to address the limitations, such as stimulation-induced side effects, by delivering selective, focal modulation via segmented contacts. However, DBS programming becomes more complex and time-consuming for clinical feasibility. Local field potentials (LFPs) might serve a functional role in guiding clinical programming. Objective: In this pilot study, we investigated the spectral dynamics of directional LFPs in subthalamic nucleus (STN) and their relationship to motor symptoms of Parkinson’s disease (PD). Methods: We recorded intraoperative STN-LFPs from 8-contact leads (Infinity-6172, Abbott Laboratories, Illinois, USA) in 8 PD patients at rest. Directional LFPs were referenced to their common average and time-frequency analysis was computed using a modified Welch periodogram method. The beta band (13-35Hz) features were extracted and their correlation to preoperative UPDRS-III scores were assessed. Results: Normalized beta power (13-20Hz) and normalized peak power (13-35Hz) were found to be higher in anterior direction despite lack of statistical significance (p>0.05). Results of the Spearman correlation analysis demonstrated positive trends with bradykinesia/rigidity in dorsoanterior direction (r=0.659, p=0.087) and with axial scores in the ventromedial direction (r=0.812, p=0.072). Conclusion: Given that testing all possible combinations of contact pairs and stimulation parameters is not feasible in a single clinic visit, spatio-spectral LFP dynamics obtained from intraoperative recordings might be used as an initial marker to select optimal contact(s).